Territory use and mineral exploitation: mobilization and popular consultation in Mercaderes, Cauca (Colombia) - Florez, Oscar Esteban Herrera; Cataia, Márcio (Geografares, 2026)
The legitimate mining popular consultation of Mercaderes, Cauca (Colombia), held in 2019, emerged as a process of community reaffirmation within the framework of an environmental conflict. This process consolidated dynamics of defense and resistance, accompanied by the radicalization of horizontal solidarities. This article demonstrates the existence of a dialectical movement in the configuration of political geography in Mercaderes, Cauca, with social mobilization and territorial conflicts at its core, arising from the threat of appropriation of the territory for its feasibility as a mineral resource. The emergence of hydrocarbon and mining exploitation processes contrasts with the loss of river springs in the municipality, hydric stress, and the arrival of illegal mining activity that profoundly affected the Sambingo River and the social dynamics associated with it. The legitimate popular consultation on mining, within an adverse social context, upheld the community’s plans and its conception of its territory.
Keywords: political economy of land; mining; environmental conflicts; social mobilization